The Role of Algerian territorial Collectivities in Valuing Their internal Financial Resources a case study of Bouira municipality,2014-2020 - Bouali , Abdenour; yahiaoui, Nacira (Journal of Research in Finance and Accounting, 2026)
The study attempted to highlight the role played by the territorial collectivities in valuing their internal resources, as we studied the case of the municipality of Bouira for the period (2014-2020), relying on the descriptive analytical approach to address the problem of the study. The study found that the internal financial resources do not live up to the required level and remain weak due to the absence of valuing the properties and rents of the territorial collectivities in the symbolic dinar, and they do not benefit from the most important taxes and fees such as the tax on corporate profits. It requires the inevitability of valuing the property of the territorial collectivities.